COMPETITIVENESS OF A RURAL TOURIST DESTINATIONS - Vuković, Predrag; Arsić, Slavica; Cvijanović, Drago (Economics of Agriculture, 2010)
Tourism has become the leading economic sector of many countries. This is witnessed by the country's revenues realized, as well as many other indicators. In the nineties of the twentieth century, the emphasis in the tourist development was placed on tourism of specific interests, as opposed to the hitherto dominant mass tourism. Noticeable is the increased demand for new forms of tourism additional offers that contemporary (urban) tourists harder, and who can offer a large part in rural areas. Development of rural tourism has given good results in Western European countries. Bearing this in mind, today there are a large number of economically less developed countries that have lost the race in industrial development with a highly developed countries, and that their chance see in development of rural tourism. Such a position are based on the ecological preservation of the rural areas, anthropogenic rich rural heritage, and the degree of industrialization which is in lags behind from the developed countries of Western Europe and America. In paper work was conducted defining rural tourism and identified factors which have influence to the strengthening of the competitiveness of some rural tourist destination with special emphasis on ecology and sustainable development.